Actualization of Situational Leadership in Handling Covid-19 and National Economic Recovery to Improve Community Welfare in the Context of Realizing a Resilient Indonesia - Sugiarto Sugiarto; Amin Lestari; M. Riza Fachlevi (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2021)
This paper aims to find out the problem of actualizing situational leadership in handling Covid-19 and national economic recovery to improve people's welfare in the context of realizing a resilient Indonesia. Before the data was analyzed, the data normality test was performed using the Kolmogorov-Smirnov test. In addition, several classical assumption tests were carried out, namely the heteroscedasticity test and the autocorrelation test. Tests on the validity and reliability of the data were carried out to determine the validity of the questionnaire to the study's objectives and show the measuring instrument's consistency in measuring the same symptoms. Then, the hypothesis test was carried out with multiple linear analyses by comparing the results of t count (t-hit) against t table (t-tab).